Addressing the patient experience in myocardial perfusion scintigraphy - Grilo, Ana Monteiro (2019)
Background: Myocardial Perfusion Scintigraphy is a medical exam whose purpose is to evaluate myocardial perfusion. This examination due to their procedures can generate some anxiety in patients that can disturb the good performance of the exam. The main objective of this study is to perform an analysis of patient's undergoing myocardial perfusion scintigraphy experience, assess patient`s anxiety and check Nuclear Medicine Department communication and information effectiveness. Material and methods: For this study, the State-Trait Anxiety Inventory (STAI) and two Scan Experience Questionnaires were used. Sixty patients answered the questionnaires before and after myocardial perfusion scintigraphy. Results: Patients reported medium levels of scan-related anxiety and trait anxiety before the myocardial perfusion scintigraphy. After the scan, there is a slight decrease in patients' anxiety. Results of the scan, radiation used, duration of the scan and the injection of the radiopharmaceutical are the most relevant patients' concerns before the scan. 15% of the sample did not receive the necessary information or the most effective way. Conclusions: The results suggest that there are several factors that tend to trigger the patient's experience and anxiety. Strategies to improve patient myocardial perfusion scintigraphy experience at Nuclear Medicine Department are presented.